Carbapenemase-Producing Enterobacteriaceae (CPE) Newborn Colonization in a Portuguese Neonatal Intensive Care Unit (NICU): Epidemiology and Infection Prevention and Control Measures - Teresa L. Almeida; Tânia Mendo; Raquel Costa; Cristina Novais; Mónica Marçal; Filomena Martins; Madalena Tuna (MDPI AG, 2021)
Infections due to carbapenemase-producing Enterobacterales (CPE) are increasing worldwide and are especially concerning in a neonatal intensive care unit (NICU). Risk factors for CPE gut colonization in neonates need to be clarified. In this work, we describe the epidemiological and clinical features of CPE-colonized newborns and the infection control measures in a Portuguese NICU. We performed a prospective, observational, longitudinal, cohort study for surveillance of CPE colonization. Maternal and neonatal features of colonized newborns and surveillance strategy were described. A statistical analysis was performed with SPSS23.0, and significance was indicated by p-value ≤ 0.05. Between March and November 2019, CPE was isolated in 5.8% of 173 admitted neonates. Carbapenemase-producing Klebsiella pneumoniae were the most frequently isolated. There was no associated infection. Birth weight, gestational age, length of stay, and days of central line were the identified risk factors for CPE colonization (bivariate analysis with Student's t-test or Mann-Whitney U test, according to normality). No independent risk factors for CPE colonization were identified in the logistic regression analysis. CPE colonization risk factors are still to be determined accurately in the neonatal population. Active surveillance and continuous infection control measures restrained the current cluster of colonized newborns and helped to prevent infection and future outbreaks.